Kinetic Analysis of Anaerobic Digestion of Rice Husk for Prediction of Methane Yield: Analisis Kinetika Pencernaan Anaerobik Sekam Padi untuk Prediksi Hasil Metana - Shitophyta, Lukhi Mulia; Nurillah, Nidha Amalia; Agustina, Evi; Purwanti, Siwi; Triyastuti, Meilya Suzan (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2023)
A study of three kinetic models for predicting methane yield was performed. The selected models for predicting methane yield were first-order, modified Gompertz and Monod models. Anaerobic digestion of rice husk was simulated using the selected models. A comparative evaluation of the models was undertaken to determine the best-fit model. All models obtained an accuracy of predicted methane yield of over 0.9. The prediction of methane yield on rice husk has the most accurate model being the modified Gompertz with the least deviation of 7.37% and the least accurate model being the Monod model with the highest deviation of 20.39%.